Genotype-environment interaction and sexual dimorphism in the genetic evaluation of yearling weight in Simmental cattle raised in Brazil - Moura, G. F.; Arce, C. D. Silva [UNESP]; Santos, J. C.G. [UNESP]; Santos, D. J. Abreu [UNESP]; Aspilcueta-Borquis, R. R.; Pegolo, N. T.; Gomide, A. P.C.; Marques, L. F.A.; Oliveira, H. N. [UNESP]; Araujo Neto, F. R. (Cambridge University Press (CUP), 2023)
The aim of this study was to evaluate the effect of genotype-environment interaction (GEI) on the yearling weight of Simmental cattle raised in Brazil, including the sex dimorphism in reaction norm models. The environmental gradient (EG) was formed using the average weight at 365 days of the contemporary groups. Two approaches were adopted in this study to evaluate reaction norms for weight at 365 days: a single-trait model and a multitrait model in which the data for males and females were separated and considered different traits for the analysis of sexual dimorphism. The genetic parameters were estimated using the Bayesian inference and Gibbs sampling. Analysis of the trend of the heritability estimates obtained with the single-trait model along the EG revealed a value of about 0.33 (EG: -21) in the worst environments, which decreased in the intermediate environments and reached a value of 0.24 in EG: -8, with a subsequent increase of the estimates up to 0.51 in EG +23. Using the multitrait model, similar trends were observed for the heritability estimates, which ranged from 0.25 to 0.54 for males and from 0.23 to 0.50 for females. The results show that the weight of Simmental cattle raised in the tropics is influenced by GEI and greater genetic progress could be obtained by selecting in better environments. However, no significant differences in the response to most environmental changes were observed between sexes and there is only evidence of genetic heteroscedasticity in environments with lower production levels.
Keywords: Animal breeding; Beef cattle; Plasticity; Reaction norm